2013
DOI: 10.7547/1030036
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Forefoot Off-loading Postoperative Shoe on Muscle Activity, Posture, and Static Balance

Abstract: The posterior shift in center of pressure toward and behind the ankle joint axis is believed to result in the increase in tibialis anterior muscle activity that now acts as the primary stabilizer around the ankle. Instability may, therefore, increase in patients with weak tibialis anterior muscles (eg, diabetic neuropathy) who need to wear offloading devices for ulcer management. We suggest that the addition of a contralateral shoe raise fitted with a FOPS may potentially be beneficial in maintaining stability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…18 Concerns have also been raised with regard to unsteadiness and increased risk of falls in patients receiving the reverse camber shoe as part of their postoperative care. 12…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…18 Concerns have also been raised with regard to unsteadiness and increased risk of falls in patients receiving the reverse camber shoe as part of their postoperative care. 12…”
mentioning
confidence: 99%
“…18 Concerns have also been raised with regard to unsteadiness and increased risk of falls in patients receiving the reverse camber shoe as part of their postoperative care. 12 Where difficulty with the reverse camber postoperative shoe has been encountered due to discomfort or unsteadiness, an alternative flat-sole postoperative shoe design has been used in our practice. This alternative design is known to have the least effect on patient gait when compared with normal footwear and is anecdotally better tolerated by the patient.…”
mentioning
confidence: 99%
“…As expected, orthopedic shoes sold in pairs may limit the problems of limb length discrepancies created by wearing a single orthopedic shoe. [ 16 - 18 , 20 , 21 ] There is also existing evidence for the use of heeled shoes, which provide significantly more forefoot offloading (between 2.5 and 4 times more depending on the design) compared to rocker bottom soles. [ 22 ] The findings of this study support the use of heel offloading shoes to acquire the highest degree of forefoot offloading, although rocker bottom shoes provided more speed in pairs.…”
Section: Discussionmentioning
confidence: 99%
“…The use of FOS is recommended after surgery to unload the anterior part of the foot, in case of injuries and ulcers, and for conservative treatments. While the effectiveness of the half-shoe in reducing forefoot pressure has been demonstrated extensively, concerns have been raised over the peculiar design of the outsole, which features a high heel and a low-profile elevated outsole in the forefoot region, thus potentially causing unstable and inefficient gait dynamics and affecting wearing comfort [ 16 ]. These factors have become increasingly important in the design of orthopaedic footwear, and are particularly critical when dealing with elderly patients with pre-existing balance problems, hence at higher risk of fall.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that wearing elevated orthopaedic shoes causes higher loads in the lower limb joints and significantly increases hip adduction and pelvic tilt on the ipsilateral side, unless it is compensated by an equivalent heel height on the contralateral foot [ 15 ]. More recently, stability and risk of falls in the half-shoe have been investigated by analysing the modifications in body dynamics and foot pressure [ 16 ].…”
Section: Introductionmentioning
confidence: 99%